2006
DOI: 10.1111/j.1439-0388.2006.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Ankamali pigs of India using microsatellite markers and their comparison with other domesticated Indian pig types

Abstract: Ankamali pigs, the domesticated native pigs of Kerala province of India were genetically characterized using 23 FAO recommended microsatellite markers and were compared with other native Indian pig types and Large White pigs. Twenty-six blood samples were collected from genetically unrelated animals from their breeding tract and DNA was isolated by standard procedure of phenol/chloroform. The genomic DNA was amplified by polymerase chain reaction (PCR) at these 23 microsatellite loci, which were also used earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The genetic diversity of LWY pigs or other European pig breeds were also reported in various other studies (Fredholm et al, 1993;van Zeveran et al, 1995;Laval et al, 2000;Martinez et al, 2000). However, the high genetic diversity have been reported earlier in Desi and Gahuri pigs by us (Behl et al, 2002 andBehl et al, 2006) and also in Chinese and Mexican pig populations (Lemus Flores et al, 2001;Fang et al, 2005). A total of 23 and 22 private alleles were observed for Niang Megha and Tenyi Vo pigs, respectively.…”
Section: Genetic Variability Of Microsatellite Locisupporting
confidence: 71%
“…The genetic diversity of LWY pigs or other European pig breeds were also reported in various other studies (Fredholm et al, 1993;van Zeveran et al, 1995;Laval et al, 2000;Martinez et al, 2000). However, the high genetic diversity have been reported earlier in Desi and Gahuri pigs by us (Behl et al, 2002 andBehl et al, 2006) and also in Chinese and Mexican pig populations (Lemus Flores et al, 2001;Fang et al, 2005). A total of 23 and 22 private alleles were observed for Niang Megha and Tenyi Vo pigs, respectively.…”
Section: Genetic Variability Of Microsatellite Locisupporting
confidence: 71%
“…From the 18 microsatellite loci analyzed, nine presented high polymorphism (PIC>0.7) and only two had PIC lower than 0.6. According to Botstein et al (1980)'s classification, markers with PIC superior to 0.5 are considered very informative; therefore, all loci used in this study were informative. The highest PIC values (0.939 and 0.903) corresponded to the microsatellites that presented higher allele numbers (S0005 and S0068, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2005) found a strong relation between Korean pigs and the Berkshire and Landrace commercial breeds, and results obtained by Behl et al (2006) identified a distinct type of Indian pig. Such examples reinforce the value of using microsatellite markers in studies focused on the characterization and conservation of animal genetic resources.…”
Section: Introductionmentioning
confidence: 91%
“…Analyzing three local and one commercial pig breeds in India with 23 microsatellite markers, Behl et al (2006) found higher values of expected heterozygosity (0.74 to 0.83) and an effective number of alleles varying between 4.78 and 5.34. On the other hand, Fang et al (2005) obtained a lower mean value for this same parameter (0.50) and the effective number of alleles found was from 1.69 to 4.76, when analyzing 32 Chinese native breeds, three commercial breeds and two wild types with 34 microsatellite markers.…”
Section: Discussionmentioning
confidence: 97%
“…Until now, among all the types of molecular markers, the microsatellite loci are the most widely used when studying the genetic diversity and population structure of livestock (Jordana et al, 2003;Yang et al, 2003;Parker et al, 2004;Martínez et al, 2006;Peter et al, 2007;Li et al, 2004;Kim et al, 2005;Behl et al, 2006). Although the Brazilian naturalized pig breeds have been little studied it is known that they present adaptation traits that could be useful in breeding programs aiming at future consumer demands.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%